OPINIONS AND BEHAVIOR OF STUDENTS IN SOCIAL ASPECTS OF INTERNET USE IN SERBIA AND SLOVENIA - Jošanov, Borislav; Pucihar, Andreja; Jošanov-Vrgović, Ivana (International Journal of Economic Practice and Policy, 2014)
Rapid involvement of Internet infrastructure and services brought a lot of new products based on information and communication technologies. In the focus of world’s social interest at this time are social networks and WikiLeaks and their abuse. In this paper authors analyze opinions and behaviour of students at Novi Sad Business School, Serbia, and Faculty of Organizational Sciences in Kranj, Slovenia. This research focuses on different kinds of abuse of social networks and WikiLeaks. Results are presented and analyzed according to the place where examinees study. Conclusions about the differencies found between the above-mentioned two groups are compared to the social states and events in these 2 countries which oficially separated 25 years ago.